Health Risk Behaviors Associated With Agrochemical Exposure Among Rice Farmers in a Rural Community, Thailand: A Community-Based Ethnography. (November 2014) - Raksanam, Buppha; Taneepanichskul, Surasak; Robson, Mark G.; Siriwong, Wattasit
The study objective was to evaluate health beliefs and behaviors associated with agrochemical exposure among rice farmers. We applied the Health Belief Model, community-based ethnography, and public health risk assessment for this study. Data were collected from 101 rice farmers in Khlong Seven community between January and June 2010. Data comprised observations, unstructured and semistructured interviews, and focus group discussions. We showed that farmers had moderate levels of perceived susceptibility to, severity of, benefits of, and barriers to using agrochemicals safely. The major risk factors related to agrochemical exposure resulted from the misuse of pesticides, including erroneous beliefs of farmers regarding pesticide toxicity, the use of faulty spraying equipment, the lack of proper maintenance of spraying equipment, or the lack of protective gear and appropriate clothing. An intervention program is necessary to improve safety with regard to agrochemicals in the rice Khlong Seven community.